Virtuous Argumentation and Unendorsed Claims - Aberdein, Andrew (Informal Logic, 2025)
Should virtuous arguers reason from premises they do not endorse? Can virtuous arguers reason to conclusions they do not endorse? Should competitive debate require participants to do either? This paper argues that, while bad faith argumentation is vicious, reasoning to or from claims that the arguer does not endorse can be undertaken virtuously. Indeed, when conducted with integrity, the capacity to trace the consequences of an opposing position is unavoidable in discharging the adversarial function of argumentation.